Wage-Price Dynamics and Structural Reforms in Japan - Porcellacchia, Davide (Washington, D.C. : International Monetary Fund, 2016)
Structural reforms in the liquidity trap need not be deflationary. This paper develops a simple framework to study the role that key characteristics of Japan's labor and product markets-labor-market duality and weak corporate governance-play in generating unfavorable wage-price dynamics. The model allows a discussion of whether and in what form structural reforms may contribute to Japan's short-run goal of reflating the economy. It finds that boosting inflation with structural reforms implies an unusual trade-off with employment, that is an inverted Phillips curve. Simultaneous implementation of labor-market and product-market reforms is most effective in terms of reflating the economy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet